Combining decentralized decision-making and takt production in construction planning and control to increase production flow - Lehtovaara, Joonas; Seppänen, Olli; Peltokorpi, Antti; Lappalainen, Eelon; Uusitalo, Petri (Frontiers in Built Environment, 2022)
Takt production and decentralized decision-making have been recent areas of interest in (lean) construction management research. Both have the potential to improve flow and contribute to increased production performance. Despite the interest, the efforts towards decentralization have not effectively considered the first-line workers; simultaneously, takt production studies suggest that neglection of workers’ involvement has led to implementation challenges and hampered flow. Thus, combining decentralized decision-making (including the involvement of the first-line workers) and takt production could have the potential for further improving production flow and performance. By utilizing design science research, this explorative single-case study aimed to evaluate the effect of decentralized decision-making and takt production to production flow through formulating, implementing, and validating a decentralized takt production framework. The primary data were collected from three production planning sessions, 17 semi-structured interviews, supported by site observations, resource tracking data, schedule data, cost data, and production progress reports. The framework formulation and validation were also supported by six expert workshops. The findings indicate that decentralization can be combined with takt production, aiding production flow. Good operations flow was especially aided by decentralized decision-making. These positive effects were supported by observations of improved utilization of site teams’ knowledge in planning, better commitment, communication, team-building process, and positive competition between teams. In addition, 23% duration savings were achieved in the production phase in which the framework was implemented. Also, stable resource utilization of trades was achieved. The decentralized decision-making practices were successfully implemented in the planning phase; however, the elements of decentralization were not adequately utilized in the control phase, resulting in that the intended benefits were not obtained in their full potential magnitude. An extensive effort over single projects and organizations would be needed to gain all intended benefits, while the competence to successfully operate with (decentralized) takt production increases with experience. The study makes scientific and managerial contributions to improving construction production planning and control practices and flow by exploring the combination of decentralized decision-making and takt production and by considering site teams and first-line workers’ viewpoints, which have been scarce in previous research.